2023
DOI: 10.1177/02698811231161579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma-aminobutyric acid on working memory and attention: A randomized, double-blinded, placebo-controlled, crossover trial

Abstract: Background: γ-Aminobutyric acid (GABA) is a primary inhibitory neurotransmitter that plays a significant role in the central nervous system. Studies on both animals and humans show that GABA has the pharmacological potential for reducing the impact of cognitive disorders, as well as enhancing cognitive functions and mood. However, its specific effects on human attention and working memory have not yet been extensively studied. Aims: In this randomized, double-blind, placebo-controlled, and crossover trial, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In addition, Leonte et al did not find a positive effect of GABA supplement (800 mg) on spatial attention but on temporal attention [197]. However, the improvement in temporal attention could not be replicated by Tınok et al [196].…”
Section: Gaba-enriched Fermented Foods As Neuro-therapeuticsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Leonte et al did not find a positive effect of GABA supplement (800 mg) on spatial attention but on temporal attention [197]. However, the improvement in temporal attention could not be replicated by Tınok et al [196].…”
Section: Gaba-enriched Fermented Foods As Neuro-therapeuticsmentioning
confidence: 94%
“…Even though all these studies reported convincing evidence that GABA-enriched foods can improve cognition, there are also studies reporting null or even negative results. Tınok et al could not find a positive effect of a GABA supplement (800 mg) dissolved in orange juice on spatial attention and visual working memory [196]. In addition, Leonte et al did not find a positive effect of GABA supplement (800 mg) on spatial attention but on temporal attention [197].…”
Section: Gaba-enriched Fermented Foods As Neuro-therapeuticsmentioning
confidence: 97%
“…GABA intake decreased cognitive flexibility during task switching, but there was no effect on Stroop task accuracy suggesting a nonlinear or U-shaped relationship between GABA intake and cognitive performance [70]. In a randomized, double-blinded, placebocontrolled, crossover trial the same GABA dose increased visual search time compared to the placebo but did not affect visual search accuracy, temporal attention, or visual working memory precision [71]. Furthermore, the GABA-enriched fermented Laminaria japonica intake provided a protective effect against cognitive impairment associated with dementia [72].…”
Section: Neuroprotective and Cognition-enhancing Effects Of Dietary Gabamentioning
confidence: 96%
“…It may take a long time to shift attention between two target stimuli. Hari et al ( 1999 ) first employed the rapid serial visual presentation (RSVP) task, which is a dual task including a rapid series of stimuli (Tınok et al, 2023 ). The RSVP task is generally used to test temporal attention allocation.…”
Section: Introductionmentioning
confidence: 99%